2016
DOI: 10.1111/coep.12190
|View full text |Cite
|
Sign up to set email alerts
|

ECONOMIC FREEDOM & HAPPINESS INEQUALITY: FRIENDS OR FOES?

Abstract: This article examines the relationship between economic freedom and happiness inequality for a large sample of countries. We find that economic freedom is negatively associated with happiness inequality and robust to several alternative measures of happiness inequality, including the standard deviation, mean absolute difference, coefficient of variation, and Gini coefficient. Among the economic freedom areas, legal system and sound money are negatively correlated with happiness inequality. Drawing on the Enger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 94 publications
1
21
0
3
Order By: Relevance
“…Finally, we advance the literature methodologically by suggesting a potential new instrument that can be used to examine the effect of a wide range of cultural values (e.g., social trust, religiosity, ethnolinguistic fractionalization) on numerous economic, social, and political outcomes. This is important since many recent studies document a strong correlation between institutions and cultural values such as social trust (Berggren and Nilsson ), morality (James ), attitudes toward fertility and childbearing (Basso ) and outcomes such as control perceptions (Nikolaev and Bennett ) and even happiness inequality (Bennett and Nikolaev ), to mention a few.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we advance the literature methodologically by suggesting a potential new instrument that can be used to examine the effect of a wide range of cultural values (e.g., social trust, religiosity, ethnolinguistic fractionalization) on numerous economic, social, and political outcomes. This is important since many recent studies document a strong correlation between institutions and cultural values such as social trust (Berggren and Nilsson ), morality (James ), attitudes toward fertility and childbearing (Basso ) and outcomes such as control perceptions (Nikolaev and Bennett ) and even happiness inequality (Bennett and Nikolaev ), to mention a few.…”
Section: Introductionmentioning
confidence: 99%
“…Nikolaev and Bennett [13] examined the relationship between economic freedom on happiness and inequality including large sample countries and found that economic freedom is negatively associated with happiness and inequality. Bennett and Nikolaev [19] explored the estimation between emotional Well-Beings and economic freedom by using the data from 12 sample countries from wave 2 of the World Value Survey and Economic Freedom Index. They found that people who lived in more economically free societies are more likely to report the presence of a positive effect on happiness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, Bennett and Nikolaev (2017) demonstrate that economic freedom reduces inequality of well-being using a robust set of inequality measures. This finding demonstrates that people actually report being happier under institutions of greater economic freedom and that the benefits of economic freedom on well-being aren't falling only on those in the upper ranks of the happiness distribution.…”
Section: A Tolerance and Protection Of Minority Groupsmentioning
confidence: 99%
“…However, they find that monetary reforms, legal reforms, and political globalization do not increase inequality. Bennett and Nikolaev (2017) examine six different measures of income inequality with up to 112 countries from 1970 to 2010. By studying the Standardized World Income Inequality Database, they are able to account for the uncertainty of the estimated Gini coefficients.…”
Section: Income Inequalitymentioning
confidence: 99%